Genetic Alterations That Do or Do Not Occur Naturally; Consequences for Genome Edited Organisms in the Context of Regulatory Oversight - Custers, René; Casacuberta, Josep M.; Eriksson, Dennis; Sági, László; Schiemann, Joachim (Frontiers in Bioengineering and Biotechnology, 2019)
The ability to successfully exploit genome edited organisms for the benefit of food security and the environment will essentially be determined by the extent to which these organisms fall under specific regulatory provisions. The answer to this question is considered to depend on the genetic characteristics of the edited organism, and whether the changes introduced in its genome do (or do not) occur naturally. We provide here a number of key considerations to assist with this evaluation as well as a guide of concrete examples of genetic alterations with an assessment of their natural occurrence. These examples support the conclusion that for many of the common types of alterations introduced by means of genome editing, the resulting organisms should not be subject to specific biosafety regulatory provisions whenever novelty of the genetic combination is a crucial determinant.